2013
DOI: 10.1002/jhbp.8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and problems in the management of pancreaticobiliary maljunction: feedback from the guidelines committee

Abstract: Clinical practice guidelines on how to deal with pancreaticobiliary maljunction (PBM) were made in Japan in 2012, representing a world first. Using a narrow definition, congenital biliary dilatation involves only Todani type I (except type Ib) and type IV-A, both of which are accompanied by PBM in almost all cases. Prospective ultrasonographic study revealed that the maximum diameter of the common bile duct increased with age. Pathophysiological conditions due to pancreatobiliary reflux occur in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
0
30
0
3
Order By: Relevance
“…Since the maximum diameter of the common bile duct correlates positively with age, standard values for the maximum diameter of the common bile duct in each age group appear appropriate for accurate evaluation of the presence of bile duct dilatation [20][21][22].…”
Section: Diagnostic Criteria For Pbm 2013mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the maximum diameter of the common bile duct correlates positively with age, standard values for the maximum diameter of the common bile duct in each age group appear appropriate for accurate evaluation of the presence of bile duct dilatation [20][21][22].…”
Section: Diagnostic Criteria For Pbm 2013mentioning
confidence: 99%
“…Cholecystectomy and resection of the extrahepatic bile duct (flow-diversion surgery) is an established standard for the surgical treatment of congenital biliary dilatation [3,22]. Internal drainage operations have been abandoned because of the high risk of postoperative carcinogenesis.…”
Section: Treatment Of Pbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that biliary tract cancers preferentially develop at sites where there is stasis of activated pancreatic enzymes. Thus, it is generally perceived that the likelihood of the development of both bile duct cancer and gallbladder cancer increases in AUPBD patients with choledochal cyst, whereas there is a significant predilection for gallbladder cancer to occur in AUPBD patient without choledochal cyst [8][9][10]. As a result, prophylactic flow-diversion surgery consisting of extrahepatic bile duct resection and bilioenteric anastomosis along with cholecystectomy is acknowledged as the treatment of choice for AUPBD patients with choledochal cyst [8].…”
Section: Introductionmentioning
confidence: 97%
“…As most biliary tract cancers that develop in patients with PBM without biliary dilatation are gallbladder cancers, only prophylactic cholecystectomy is performed in many institutions. However, in some institutions, because of a perceived risk of bile duct cancer, the extrahepatic bile duct is excised together with the gallbladder [1,4,26,35].…”
Section: Treatment Of Pbmmentioning
confidence: 99%